Valorization of oil palm empty fruit bunch (OPEFB) as membrane polymer via non-solvent induced phase separation method (NIPS) for removal of aqueous contaminants - Sjahro, Noerhidajat; Yunus, Robiah; Abdullah, Luqman Chuah; Nainggolan, Marihot; Abdul Rashid, Suraya; Asis, Ahmad Jaril; Syafiie, S.; Habib, Saiful Hafiz; Harun, Nurhanina (Springer Nature, 2025)
Oil palm empty fruit bunches (OPEFB) is byproducts from the palm oil processing mills currently discarded on field with less economic value. Meanwhile, it has a potential as precursor for cellulose feedstock as a membrane main polymer due to its biodegradability, environmental benign, and renewability. However, due to its insolubility in most available solvents, its utilization as a primary polymer matrix is limited. In this study, we transformed native and functionalized cellulose derived from OPEFB into membrane via non-solvent induced phase separation (NIPS) using trifluoroacetic acid (TFA) and dichloroethane (DCE) as the solvent. The fabrication parameters included duration of air exposure ranging for 2,3, and 4 min prior to water immersion for 24 h; and membrane composition, consisting of cellulose as main polymer, TiO2 and PEG as additives. Based on TGA analysis, it suggests that membrane of pure cellulose has the highest decomposition temperature, while FTIR spectra of the synthesized membranes indicate complete dilution of TFA & DCE during water immersion. The membranes were characterized to have water affinity indicating hydrophilic properties with water contact angle ranging from 16.12° to 26.4°. The membrane maximum water flux rate accounted for 172.6 L/m2 h bar, while ion removal for Pb2+ Cu2+ and Cr3+, dye ranged from 87.3 to 98.9%, 83.98 to 99.28%, 93.6 to 99.9%, 94.3 to 99%, respectively. Meanwhile, oil rejection ranged from 98.03 to 99.36%. Thus, it can be concluded that OPEFB derived cellulose as main polymer matrices for membrane have a great potential for wastewater treatment and water purification area.